An Antiproteolytic and Antifibrinolytic Preparation Obtained from the Potato by Means of Chromatography on SE-Sephadex C-50 - Worowski, K (Thrombosis and Haemostasis, 1974)
A crude preparation of a proteolytic enzyme inhibitor from potatoes was purified by means of column chromatography with SE-Sephadex C-50 using a stepwise gradient of concentration and pH when eluting proteins from the column. The inhibitor preparation thus obtained is stable for a 28 day period of storage and resistant to the action of various physical and chemical factors harmful to the spatial structure of proteins. The potato protease inhibitor markedly inhibits the activity of trypsin, chymotrypsin, plasmin and alkaline proteases from Aspergillus flavus. The inhibition of pronase and a mixture of acid cellular proteases by this inhibitor is considerably less. Pepsin, cathepsin D, and collagenase are not affected by this inhibitor. The potato inhibitor has a marked inhibitory effect on plasmin fibrinolytic activity both in purified systems and in the plasma euglobulin fraction. It also protects the fibrinogen from the action of this enzyme. It does not, however, inhibit plasminogen activation under the influence of either streptokinase or urokinase.